Aspects of digital change - Hoare, Adam (Cambridge Scholars Publishing, 2019)
Digital change is a notoriously difficult endeavour to undertake. The public sector has engaged in many projects to embrace digitalisation. These include projects in health and social care, the benefits system, EU farm subsidy payments and child support payments, to name a few. Project timescales and budgets are over-run and aspects of the projects are sometimes abandoned with many millions of pounds sunk. In the private sector, companies such as Amazon use 'test and learn' approaches to build technology platforms that deliver real person-centred services.